The Effect of Transformational Leadership on Crisis Management at Al-Thawra General Hospital Authority, Hodeidah Governorate, Republic of Yemen - Mohammed Qaid Ahmed Al-Lima; Resal Yahya Fadhel (University of Science and Technology, Sana’a, Yemen, 2024)
This study aimed to investigate the impact of transformational leadership on crisis management at Al-Thawra General Hospital Authority in Hodeidah. It also explored potential variations in crisis management perception based on employee demographics (gender, qualification, job title, and experience). A descriptive analytical approach was employed. The target population consisted of all Al-Thawra Hospital employees (n=1362). A sample of 300 individuals (22%) was selected. A pilot study (n=30) assessed validity and reliability before main data collection. Data analysis using SPSS revealed a significant positive impact of transformational leadership dimensions on crisis management. Besides, during a crisis, male employees exhibited higher confidence in crisis response compared to females. Additionally, employees with less than five years of experience displayed a stronger perception of their ability to contribute to crisis management across various phases. Based on these findings, the study recommends that Al-Thawra leadership prioritize the development of transformational leadership skills and implement a comprehensive crisis management plan encompassing all crisis stages.